Fostering Positive Student Characters in Preserving Cultural Traditions Through the Wrespati Meprani Program at SMP Negeri 2 Bangli - Gama, Putu Gede; Perbowosari, Heny (Jayapangus Press, 2023)
Educational institutions are not only teaching students knowledge and skills but also teach students to have good character and love their own cultural traditions. Educators feel the need to anticipate by involving students in activities related to cultural traditions. This is based on current conditions where the development and existence of technology in the digital era can be a threat to student character. Fostering positive student character is one of the important things and is of full concern to character education observers both from the government and the wider community. This is because character education can shape students into individuals with good character and high moral values, so that they can become a superior and highly competitive generation. SMP Negeri 2 Bangli has a school program called Wrespati Meprani which aims to foster positive student character and preserve cultural traditions. The Wrespati Meprani program can foster positive character in students, such as religious character, respect, discipline, cooperation, creativity, self-confidence, sense of responsibility and respect for cultural values. The research carried out is qualitative research, data sources are obtained from some of the information collected. In this study, the primary data are the results of interviews with research subjects such as interviews with principals, teachers and students who are considered to have a relationship with the problems to be studied. Secondary data in this study are books that are relevant and related to the problem to be studied. The message contained in the Wrespati Meprani program is that the school community is able to understand and interpret the values contained in it so that the Meprani tradition is always maintained and preserved.